Cellular and extracellular proteomic profiling of paradoxical low-flow low-gradient aortic stenosis myocardium - Elkenani, Manar; Barallobre-Barreiro, Javier; Schnelle, Moritz; Mohamed, Belal A.; Beuthner, Bo E.; Jacob, Christoph Friedemann; Paul, Niels B.; Yin, Xiaoke; Theofilatos, Konstantinos; Fischer, Andreas; Puls, Miriam; Zeisberg, Elisabeth M.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Aims Patients with severe aortic stenosis (AS), low transvalvular flow (LF) and low gradient (LG) with normal ejection fraction (EF)—are referred to as paradoxical LF-LG AS (PLF-LG). PLF-LG patients develop more advanced heart failure symptoms and have a worse prognosis than patients with normal EF and high-gradient AS (NEF-HG). Despite its clinical relevance, the mechanisms underlying PLF-LG are still poorly understood. Methods Left ventricular (LV) myocardial biopsies of PLF-LG (n = 5) and NEF-HG patients (n = 6), obtained during transcatheter aortic valve implantation, were analyzed by LC-MS/MS after sequential extraction of cellular and extracellular matrix (ECM) proteins using a three-step extraction method. Proteomic data are available via ProteomeXchange with identifier PXD055391. Results 73 cellular proteins were differentially abundant between the 2 groups. Among these, a network of proteins related to muscle contraction and arrhythmogenic cardiomyopathy (e.g., cTnI, FKBP1A and CACNA2D1) was found in PLF-LG. Extracellularly, upregulated proteins in PLF-LG were related to ATP synthesis and oxidative phosphorylation (e.g., ATP5PF, COX5B and UQCRB). Interestingly, we observed a 1.3-fold increase in cyclophilin A (CyPA), proinflammatory cytokine, in the extracellular extracts of PLF-LG AS patients (p < 0.05). Consistently, immunohistochemical analysis confirmed its extracellular localization in PLF-LG AS LV sections along with an increase in its receptor, CD147, compared to the NEF-HG AS patients. Levels of core ECM proteins, namely collagens and proteoglycans, were comparable between groups. Conclusion Our study pinpointed novel candidates and processes with potential relevance in the pathophysiology of PLF-LG. The role of CyPA in particular warrants further investigation.